Analisis Konseptual Landasan dan Prinsip-Prinsip Pengembangan Kurikulum Pendidikan Agama Islam - Mardiah Astuti; Khoirunnisah, Alya; Rani Mega Utami; Ratu Triana Ulya; Saskia Melandri; Vidya Daniati; Fernando; Dinda Alisa Pertiwi (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
The curriculum is a fundamental element in the education system that directs all learning activities towards national education goals. In the context of Islamic Religious Education (IRE), the curriculum plays an important role in shaping the personality of Muslims who are faithful, pious, and have noble character. This article aims to conceptually analyze the foundations and principles of PAI curriculum development through a qualitative approach based on literature studies. The results of the study show that PAI curriculum development must be based on philosophical, theological, psychological, sociological, and science and technology (IPTEK) foundations. In addition, principles such as relevance, effectiveness, efficiency, continuity, flexibility, and learner-centeredness are the main guidelines in curriculum development. Based on Islamic values and taking into account the developments of the times, the PAI curriculum is expected to be able to shape learners who are not only intellectually intelligent but also excel in moral and spiritual aspects.